Role of cathepsin S In periodontal wound healing-an in vitro study on human PDL cells - Svenja Memmert; Marjan Nokhbehsaim; Anna Damanaki; Andressa V. B. Nogueira; Alexandra K. Papadopoulou; Christina Piperi; Efthimia K. Basdra; Birgit Rath-Deschner; Werner Götz; Joni A. Cirelli; Andreas Jäger; James Deschner (BMC, 2018)
Abstract Background Cathepsin S is a cysteine protease, which is expressed in human periodontal ligament (PDL) cells under inflammatory and infectious conditions. This in vitro study was established to investigate the effect of cathepsin S on PDL cell wound closure. Methods An in vitro wound healing assay was used to monitor wound closure in wounded PDL cell monolayers for 72 h in the presence and absence of cathepsin S. In addition, the effects of cathepsin S on specific markers for apoptosis and proliferation were studied at transcriptional level. Changes in the proliferation rate due to cathepsin S stimulation were analyzed by an XTT assay, and the actions of cathepsin S on cell migration were investigated via live cell tracking. Additionally, PDL cell monolayers were treated with a toll-like receptor 2 agonist in the presence and absence of a cathepsin inhibitor to examine if periodontal bacteria can alter wound closure via cathepsins. Results Cathepsin S enhanced significantly the in vitro wound healing rate by inducing proliferation and by increasing the speed of cell migration, but had no effect on apoptosis. Moreover, the toll-like receptor 2 agonist enhanced significantly the wound closure and this stimulatory effect was dependent on cathepsins. Conclusions Our findings provide original evidence that cathepsin S stimulates PDL cell proliferation and migration and, thereby, wound closure, suggesting that this cysteine protease might play a critical role in periodontal remodeling and healing. In addition, cathepsins might be exploited by periodontal bacteria to regulate critical PDL cell functions.